Fine tuning of magnetization relaxation parameters of the DyO+single ion magnet in a hydroxy/fluoro-apatite solid solution - Kazin, Pavel E.; Zykin, Mikhail A.; Trusov, Lev A.; Vasiliev, Alexander V.; Kolesnik, Irina V.; Schnelle, Walter; Felser, Claudia; Jansen, Martin (Crystengcomm, 2019)
DyO + embedded in a hydroxy/fluoro-apatite matrix reveals robust and finely tunable single-ion-magnet properties. The energy barrier for magnetization reversal grows with the increase in the fluoride and Dy content. A high Dy concentration slows down the quantum tunneling of magnetization, contrary to a commonly observed trend for its acceleration.
CRIS-Team Scopus Importer:2022-04-14